Odpowiedzi

2010-02-17T14:40:46+01:00
A) -7x -14 +4= -3x
-7x + 3x= 14 -4
-4x= 10 /(-4)
x=10:4
b) 1-[(2x+5)/3]=4 /×3
1-(2x+5)= 12
-2x-5=12-1
-2x=11+5
-2x=16 /(-2)
x=-8
c) -4(½x-2)-4=2(-x+2)
-2x+8-4= -2x+4
0=0
d) 2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²+3x-x-3)
2x²-2x=2x²=6x-2x-6
2x²-2x²-2x-6x+2x=-6
-6x=-6 /(-6)
x=1
e) (x/2)-(x/3)+1=⅙(x+6) /6
3x-2x+6=x+6
3x-3x=6-6
0=0
f) [(x-1)/4]-[(x+1)/2]=-(x/4) /4
x-1-2(x+1)=-x
2x-2x=3
0=3 - sprzecznosc
Najlepsza Odpowiedź!
2010-02-17T14:41:32+01:00
A) -7(x+2)+4=-3x
-7x-14+4= -3x
-7x+3x=14-4
-4x=10/:(-4)
x= -2,5

b) 1-[(2x+5)/3]=4 /*3
3-6x+15=4
-6x=-3-15+4
-6x=-14 /:(-6)
x=2,33


c) -4(½x-2)-4=2(-x+2)
-2x-4=-2x+4
-2x+2x=4+4
0=8

d) 2x(x-1)=2(x-1)(x+3)
2x^2-2=(2x-2)(x+3)
2x^2-2=2x^2-6+4x
2x^2-2x^2+4x=2-6
4x=-4 /:4
x=-1

e)(x/2)-(x/3)+1=⅙(x+6) /*6
3x-2x+6=x+6
x-x=-6+6
0=0

f) [(x-1)/4]-[(x+1)/2]=-(x/4) /*4
x-1-2x+1=-x
x-2x+x=1-1
0=0

Najj za to :D

2010-02-17T15:06:42+01:00
A) -7(x+2)+4=-3x
-7x-14+4=-3x
-7x+3x=14-4
-5x=10/(-5)
x=-2

b) 1-[(2x+5)/3]=4
1(-2x-5)/(-3)=4
-2x-5/(-3)=4
-2x+1 i 2/3=4
-2x=4-1 i 2/3
-2x=4/1*3 - 5/3
-2x=12/3-5/3
-2x=2 i 1/3|/-2
x = -1


c) -4(½x-2)-4=2(-x+2)
-2x+8-4=-2x+4
-2x+2x=-8+4+4
x=0


d) 2x(x-1)=2(x-1)(x+3)
2x² -2x=2*x²+3x-1x-3
2x²-2x-2x²-3x-1x=-3
-6x=-3|/(-6)
x=0,5


e) (x/2)-(x/3)+1=⅙
nie jestem pewna jak rozwiązaci



f) [(x-1)/4]-[(x+1)/2]=-(x/4)
yo nie wiem jak rozwiązać


mam nadziej że chociaż trochę pomogłam